Case Report: Spontaneous pneumomediastinum in a patient with MDA5-positive dermatomyositis and severe pulmonary fibrosis - Rizzo, M.; Braga, C.; Raschellà, M.; Maranini, B.; Schifino, G.; Carnevale, A.; Govoni, M.; Lo Monaco, A. (Frontiers in Medicine, 2025)
IntroductionDermatomyositis (DM) is a rare autoimmune disorder, with the anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody positive subtype associated with severe complications such as rapidly progressive interstitial lung disease (RP-ILD) and, more rarely, spontaneous pneumomediastinum (SPM). This case highlights the challenges of managing a patient with such complex condition, particularly in the context of multiple comorbidities, including a history of cancer and recurrent infections.Case descriptionA 45-year-old woman with an history of vulvar squamous cell carcinoma (July 2022) presented with classic features of DM, including Gottron’s papules, proximal muscle weakness, dysphagia, severe cutaneous vasculitis and lymphopenia. She was then diagnosed with anti-MDA5-positive DM in October 2023. High-resolution CT (HRCT) of the lung performed in January 2024, in the absence of respiratory symptoms, revealed early interstitial changes with ground-glass opacities. Initial corticosteroid therapy yielded partial improvement. A Listeria monocytogenes meningitis in July 2024, coupled with her history of cancer, delayed the start of aggressive immunosuppressive therapy, even though the onset of dyspnea and imaging in June 2024 had already revealed worsening interstitial lung disease (ILD). In the meantime she received two cycles of intravenous immunoglobulin (IVIg). By October 2024, clinical decline with cutaneous ulcers and severe lymphopenia prompted cyclosporine (CyA) initiation. Concurrently, imaging revealed progressing ILD with new-onset pneumomediastinum and subcutaneous emphysema, culminating in massive emphysema requiring hospitalization and bilateral thoracic drainage. A multidisciplinary team approved the escalation to rituximab, which, in combination with her existing regimen, led to clinical stabilization and the resolution of her pulmonary and cutaneous symptoms.ConclusionThis case emphasizes the complexity of managing anti-MDA5-positive DM with severe pulmonary complications. Early recognition, a multidisciplinary approach, and personalized treatment are crucial to improving outcomes.